VD_FINDINFO HC / 2025 / 860 vom 11. November 2025 - VD Tribunal cantonal (2025)
JUSTE MOTIF, CONTRAT DE TRAVAIL, MAXIME DES DÉBATS | 337 al. 1 CO, 311 al. 1 CPC (CH), 317 al. 1 CPC (CH), 55 al. 1 CPC (CH)